2003
DOI: 10.1016/s0968-0896(03)00500-5
|View full text |Cite
|
Sign up to set email alerts
|

A system of protein target sequences for anti-RNA-viral chemotherapy by a vitamin B6-Derived zinc-Chelating trioxa-adamantane-triol

Abstract: The synthesis of the structurally unusual heterotricyclic compound 1-[3-hydroxy-5-(hydroxymethyl)-2-methyl-4-pyridinyl]-2,8,9-trioxaadamantane-3,5,7-triol (trivially named bananin, BN) from pyridoxylidenephloroglucinol and a theoretical prospect on possible biological activities of BN are presented in this report. Pyridoxylidenephloroglucinol is synthesized by Knoevenagel condensation of the vitamin B6 aldehyde pyridoxal with phloroglucinol. Pyridoxylidenephloroglucinol rearranges to light-yellow (4'RS)-1',4'-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…A separate Chinese study, which separated SARS-CoV patients into 4 treatment groups, identified early high-dose steroids in combination with a quinolone as producing the best patient outcomes [19]. Nevertheless, one review stated that the WHO does not currently recommend corticosteroids in other viral diseases such as Dengue as the 'glucocorticoid-mediated stimulation of the hypothalamic-pituitaryadrenal axis can also drive lymphocytopenia, or it may promote exaggerated pro-inflammatory responses that eventually cause a worsening of the pathogenic condition' [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate Chinese study, which separated SARS-CoV patients into 4 treatment groups, identified early high-dose steroids in combination with a quinolone as producing the best patient outcomes [19]. Nevertheless, one review stated that the WHO does not currently recommend corticosteroids in other viral diseases such as Dengue as the 'glucocorticoid-mediated stimulation of the hypothalamic-pituitaryadrenal axis can also drive lymphocytopenia, or it may promote exaggerated pro-inflammatory responses that eventually cause a worsening of the pathogenic condition' [20].…”
Section: Resultsmentioning
confidence: 99%
“…• ADAM-17 regulates IL-6 class switching as a mediator between pro-and anti-inflammatory responses to viral antigenic stimuli in Ebola, SARS-CoV and dengue infections in humans. Therefore, ADAM-17 should be considered as a potential target molecule for novel antiviral drug discovery for infections, such as SARS-CoV [20] • SARS-CoV ssRNA is a new therapeutic target given its capacity to cause acute lung injury in mice with a high mortality rate in vivo experiment suggesting that SARS-CoV specific GU-rich ssRNA plays a very important role in the cytokine storm associated with a dysregulation of the innate immunity [40]. • DUSP1 and p38 MAPK are potential therapeutic targets for coronavirus infectious bronchitis virus, given their capability to reduce the production of an excessive amount of IL-6 and IL-8 in the infected cells [41].…”
Section: Potential Targets For Therapeutic Intervention Related To Ilmentioning
confidence: 99%
“…The bananins were synthesized by the reaction of phloroglucinol (most likely in its triketo tautomeric form) with aromatic aldehydes, catalyzed by hydrochloric acid or sodium hydroxide in aqueous solution. 57 Generally, acidic catalysis was used due to the degradation of pyridoxal under highly basic conditions. Alkaline catalysis was used for reaction with aromatic aldehydes such as vanillin to obtain Vanillinbananin (VBN) 55.…”
Section: V I R a L U N C O A T I N G : M 2 I N H I B I T O R S ( I mentioning
confidence: 99%
“…The structurally unusual heterotricyclic compound named bananin (BN) has several roles including Zn 2+ chelator, and a target of interest is HIV-1 ZF, HIV-1 RNA-binding NC7. In addition, the targets of BN could be adsorption, transcription and/ or viral RNA replication of a interestingly wide range RNA viruses reviewed in [11]. The findings summarized in Table 2 show that various viral proteins can bind different metal ions.…”
Section: Binding Of Metal Ions With Different Virion Proteinsmentioning
confidence: 99%